Optimal location and sizing of distributed generator for loss minimization and voltage improvement in a power system using artificial immune system / Mohd Azwan Ahmad - Ahmad, Mohd Azwan (2006)
Distributed Energy Resources (DER) has becoming more popular in the transmission system nowadays. It has been focusing on their potential to influence the dynamic stability of a transmission system. A major problem with any solution for Distributed Generation (DG) is the coordination of Distributed Energy Resources (DER) to meet demand. This report present the values of Distributed Generator (DG) that are very dependent on its type, size and location as it was installed. In order to enhance the reliability and obtain the benefits for DG placement, a strategic DG placement technique is proposed in this paper. The performance of this technique is tested using 30 buses IEEE Reliability Test System. An optimization programmed written in MATLAB by using Artificial Immune System (AIS) technique was used to compute power flow. The test result shows that the location and sizing of the DG identified by the proposed technique has been able to improve voltage stability of the system and also minimize the power losses.